Diversity, distribution, and functional potentials of magroviruses from marine and brackish waters - Xu, Bu; Fan, Lu; Wang, Wenxiu; Zhu, Yuanqing; Zhang, Chuanlun (Frontiers in Microbiology, 2023)
Marine group II (MGII) archaea (Ca. Poseidoniales) are among the most abundant microbes in global oceanic surface waters and play an important role in driving marine biogeochemical cycles. Magroviruses – the viruses of MGII archaea have been recently found to occur ubiquitously in surface ocean. However, their diversity, distribution, and potential ecological functions in coastal zones especially brackish waters are unknown. Here we obtained 234 non-redundant magroviral genomes from brackish surface waters by using homology searches for viral signature proteins highlighting the uncovered vast diversity of this novel viral group. Phylogenetic analysis based on these brackish magroviruses along with previously reported marine ones identified six taxonomic groups with close evolutionary connection to both haloviruses and the viruses of Marine Group I archaea. Magroviruses were present abundantly both in brackish and open ocean samples with some showing habitat specification and others having broad spectrums of distribution between different habitats. Genome annotation suggests they may be involved in regulating multiple metabolic pathways of MGII archaea. Our results uncover the previously overlooked diversity and ecological potentials of a major archaeal virial group in global ocean and brackish waters and shed light on the cryptic evolutionary history of archaeal viruses.